Evolutionary History and Ecology of Andrena (Foveoandrena) androfovea: A New Nearctic Mining Bee (Hymenoptera, Andrenidae) Species and Subgenus - Silas Bossert; Keng‐Lou James Hung; John L. Neff (Ecology and Evolution)
ABSTRACT With about 1700 described species, the mining bee genus Andrena is a rapidly diversifying lineage and one of the most species‐rich groups of bees. Recent phylogenomic advances have greatly improved our understanding of the phylogeny of the genus, yet many species still await description, subgeneric assignments that are in line with their evolutionary history, as well as study of their morphology and behavior. Here we provide a comprehensive account of a newly discovered species, Andrena androfovea n. sp. We sequence the genome of the new species and include it in the presently most comprehensive phylogenomic analysis of Andrena using ultraconserved element (UCE) sequence data, comprising 264 samples and 249 species. Given the recovered phylogenetic position of the new species, we establish a new subgenus, Foveoandrena, provide a detailed morphological description, and discuss the antiquity and historical biogeography of the lineage in light of molecular divergence time estimates. Lastly, we study and document the foraging behavior of the new species with photos and video footage, and discuss the species' unusual host plant associations with Chamaesaracha and Quincula, both Solanaceae. Being likely oligolectic on these plants, we present the first documented case of an Andrena species being narrowly associated with members of this plant family. By integrating multiple lines of documentation, our study provides a particularly detailed account of species discovery and description.